2023
DOI: 10.1177/00332941231180119
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Loneliness and Internet or Smartphone Addiction Among Adolescents: A Systematic Review and meta-Analysis

Abstract: Background: Loneliness is a common public health problem that influences people’s physical and mental health. There is a high incidence of loneliness in adolescents. Some research suggested that smartphone or Internet addiction (SA or IA) may be a factor. But the relationship between loneliness and SA or IA is not completely clear among adolescents. We aim to estimate the correlation coefficient r between them. Methods: Databases, consisting of PubMed and Web of Science, were retrieved systematically for studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The greater the frequency of experiencing perceived loneliness, the greater the risk of developing smartphone overdependence by a factor of 1.98. Previous studies have identified perceived loneliness as a contributing factor to internet and smartphone addiction among adolescents [14], with increased levels of loneliness associated with increased time spent on smartphones [29]. Adolescents worldwide are increasingly lonely, with girls reporting more loneliness and loneliness associated with greater smartphone and internet use [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The greater the frequency of experiencing perceived loneliness, the greater the risk of developing smartphone overdependence by a factor of 1.98. Previous studies have identified perceived loneliness as a contributing factor to internet and smartphone addiction among adolescents [14], with increased levels of loneliness associated with increased time spent on smartphones [29]. Adolescents worldwide are increasingly lonely, with girls reporting more loneliness and loneliness associated with greater smartphone and internet use [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The total score ranges from 10 to 40 points, with a higher score indicating a higher level of smartphone overdependence. Based on the total score obtained, individuals can be classified into three groups: a normal group (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), a potential-risk group (23)(24)(25)(26)(27)(28)(29)(30), and a high-risk group (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). For this study, we merged the potential-risk group and high-risk group into the risk group (scores ≥ 23) and compared it with the normal group (scores < 23).…”
Section: Variables 1) Dependent Variable: Smartphone Overdependencementioning
confidence: 99%
See 1 more Smart Citation
“…People may now stay in touch with friends and family and fight loneliness and isolation thanks to the internet and smartphones. Loneliness and disconnection rise as technology replaces face-to-face interactions (Ge et al, 2023).…”
Section: Loneliness and Smartphone Addictionmentioning
confidence: 99%
“…A study of 600 primary school students found that RESE partially mediated the relationship between emotional abuse and loneliness in children [33]. Notably, there is a signi cant positive correlation between loneliness and the risk of IA among adolescents [34,35]. These ndings imply that RESE may negatively predict IA in children and may play a mediating role between emotional abuse and IA in children.…”
Section: Introductionmentioning
confidence: 97%